(untitled) (ELang | An English Language Education Journal, 2023)
This research is entitled “A Translation Analysis of English Idioms from English to Indonesia by Listiana Srisanti in the Novel Harry Potter and the Chamber of Secret by J.K Rowling”. The purpose of this research is to find out the types of idioms in Harry Potter and the Chamber of Secret novels, as well as the translation strategies used by the translator. This study uses qualitative research methods and applies descriptive analysis based on theory from O`Dell & McCarthy for idiom types, as well as theory from Baker for translation strategies. The researcher only focuses on idioms found in this novel. Here the researcher found 119 idioms in the novel. The researcher found the 7 types of idioms. They are Similes as many as 16 data or 13.45%, Binomials as many as 17 data or 14.29%, 1 data or 0.84% belongs to Trinomials type, Proverbs as many as 3 data or 2.52%, Cliches as many as 27 data or 22.69%, Fixed statements as many as 54 data or 45.38%, and 1 data or 0.84% belongs to Other languages. In addition, the researcher found 4 strategies used by the translator out of a total of 6 idiom translation strategies. They are divided into strategies that are used by the translator to translate the idiom into the target language as follows; Similar Meaning and Form (SMF) as many as 59 data (49.58%), Similar Meaning but Dissimilar Form (SMDF) as many as 44 data (36.97%), Translating by Paraphrase (TBP) as many as 15 data (12.61%), and Translating by Omission of Entire Idiom (TOE) as many as 1 data (0.84%). Based on the data, the most common type of idiom found in the novel Harry Potter and the Chamber of Secrets is the Fixed Statement. While the most dominant translation strategy is Similar Meaning and Form. The researcher chose the novel Harry Potter and the Chamber of Secrets as the object of this study for several reasons, such as the many idioms used in the novel, the easy storyline to follow, and the everyday sentences found in the dialogues in the novel.